The scandal of leadership: unmasking the powers of domination in the church - Woodward, J. R. (100 Movements Publishing, an imprint of Movement Leaders Collective, 2023)
"Will we become a scandal to those who look to us as leaders, or will we choose to imitate the scandalous way of Christ? The fall of high-profile leaders has sadly become an epidemic, and although books and podcasts have sought to uncover the problem, they often fail to identify the root cause. In The Scandal of Leadership, JR Woodward offers a deeper diagnosis, outlining a more comprehensive understanding of power abuses in the church and the critical role of imitation. Drawing from Scripture and the scholarship of Walter Wink, René Girard, and William Stringfellow, as well as from positive examples of leaders such as Óscar Romero, this book offers a robust theology of the Powers––of Satan, the demonic, and the principalities and powers explored in the Bible. By unmasking the Powers of domination, Woodward seeks to help missional leaders practice a self-emptying spirituality that reshapes their desires and forms them into Christlike servants who join God’s mission in the world.” – back cover."--